Doc Martin. Series 3 [videorecording (DVD)] - Bolt, Ben, 1952-; Clunes, Martin, 1961-; Catz, Caroline; Cole, Stephanie, 1941-; McNeice, Ian (Distributed by Acorn Media, 2010)
Dr. Martin Ellingham is brilliant, dedicated, and highly efficient. He's also brusque, abrasive, and terrified of blood. Once a successful London surgeon, he's now a GP in the idyllic Cornish fishing village of Portwenn, where he's every bit as eccentric as the villagers he serves.